1. FIRST PRINCIPLE OF MATHEMATICAL INDUCTION
The proof of proposition by mathematical induction consists of the following three steps :
Step I : (Verification step) : Actual verification of the proposition for the starting value “i”
Step II : (Induction step) : Assuming the proposition to be true for “k”, ki and proving that it is true for the value (k + 1) which is next higher integer.
Step III : (Generalization step) : To combine the above two steps Let p(n) be a statement involving the natural number n such that
(i) p(1) is true i.e. p(n) is true for n = 1.
(ii) p(m + 1) is true, whenever p(m) is true i.e. p(m) is true ⇒ p(m + 1) is true.
Then p(n) is true for all natural numbers n.
2. SECOND PRINCIPLE OF MATHEMATICAL INDUCTION
The proof of proposition by mathematical induction consists of following steps :
Step I : (Verification step) : Actual verification of the proposition for the starting value i and (i + 1).
Step II : (Induction step) : Assuming the proposition to be true for k – 1 and k and then proving that it is true for the value k + 1; k i + 1.
Step III : (Generalization step) : Combining the above two steps.
Let p(n) be a statement involving the natural number n such that
(i) p(1) is true i.e. p(n) is true for n = 1 and
(ii) p(m + 1) is true, whenever p(n) is true for all n, where
Then p(n) is true for all natural numbers.
For a b, The expression is divisible by
(a) a + b if n is even. (b) a – b is n if odd or even.
3. SOME USEFUL FORMULAS
Here are some formulas for sequences that are great for practicing proofs by induction. For any natural number n
- 1 + 2 + 3+….+ n =
- 1 + 3 + 5 + … + (2n-1) = n2
- 1 + 2 + 22 + … + 2n = 2n+1 – 1
- 12 + 22 + 32 + … + n2 =
- 13 + 23 + 33 + … + n3 = [n(n+1)/2]2
- 1*2 + 2*3 + … + n(n + 1) =
- 12 + 32 + 52 + … + (2n + 1)2 =
Illustration -1
The value of is
(A) (B) (C) (D) none of these
Solution
(C)
Let P(n)
P(1) is true
Let P(k) be true.
P(k + 1) on the L.H.S.
=
The sum within the square brackets is P(k) which equals
P(k + 1) =
= .
Which is the desired R.H.S. of P(k+1) . Hence, P(k+1) is true.
Hence, by mathematical induction, the result is true for all n.
Illustration -2
The value of is,
(A) (B) (C) (D)
Solution
(B)
Let P(n)
L.H.S. of P(1) = = R.H.S
Hence P(1) is true.
Assume that P(k) is true.
For P(k + 1), the L.H.S. becomes
=
=
Hence, by mathematical induction, the result is true for all n ∈ N
Illustration -3
The smallest positive integer n, for which hold is
(A) 1 (B) 2 (C) 3 (D) 4
Solution
(B)
Let P(n) :
Step I: For n = 2
⇒ 2 < 2.25 which is true. Therefore, P(2) is true.
Step II: Assume that P(k) is true, then P(k):
Step III: For n = k + 1, P(k + 1): (k + 1)! <
⇒ (k + 1)k! < ___________________ (i)
and ___________________ (ii)
Which is true, hence (ii) is true.
From (i) and (ii),
Hence P(k+1) is true. Hence by the principle of mathematical induction P(n) is true for all n∈N
Trick: By check options,
(A) For n = 1, 1 < 1 which is wrong
(B) For n = 2, which is correct
(C) For n = 3, 6 < 8 which is correct
(D) For n = 4,
⇒ 24 < 39.0625 which is correct.
But smallest positive integer n is 2.
Illustration -4
Let S(k) = 1 + 3 + 5 + … + (2k – 1) = 3 + k2. Then which of the following is true.
(A) Principle of mathematical induction can be used to prove the formula
(B) S(k) ⇒ S(k+1)
(C) S(k) S(k+1)
(D) S(1) is correct
Solution
(C)
We have S(k) = 1 + 3 + 5 + ….+ (2k – 1) = 3 + k2,
S(1) ⇒ 1 = 4, Which is not true and S(2) ⇒ 3 = 7, Which is not true. Hence induction cannot be applied and S(k) S(k + 1).
Illustration -5
Given , the value of for all n∈N is
(A) (B) (C) 0 (D) None of these
Solution
(B)
…..(i)
Step I : Given
For n =1, ,
Option (b)
For n = 1, which is true. For n = 2, which is true
Therefore, the result is true for n = 1 and n = 2
Step II : Assume it is true for n = k then it is also true for n = k – 1
Then …..(ii) and …..(iii)
Step III : Putting n = k in (i), we get
=
This shows that the result is true for n=k+1, by the principle of mathematical induction the result is true for all n∈N.
Illustration -6
Prove the following by using the principle of mathematical induction for all n ∈ N:
13 + 23 + 33 + …. + n3 =
Solution
Let the given statement be P(n), i.e.,
P(n): 13 + 23 + 33 + …. + n3 =
For n = 1, we have
P(1): 13 = 1 = , which is true.
Let P(k) be true for some positive integer k, i.e.,
13 + 23 + 33 + ….. + k3 = __________ (i)
We shall now prove that P(k + 1) is true.
Consider
13 + 23 + 33 + … + k3 + (k + 1)3 [Using (i)]
Thus, P(k + 1) is true whenever P(k) is true.
Hence, by the principle of mathematical induction, statement P(n) is true for all natural numbers i.e., n.
Illustration -7
Prove the following by using the principle of mathematical induction for all n ∈ N:
12 + 32 + 52 + … + (2n – 1)2 =
Solution
Let the given statement be P(n), i.e.,
P(n) = 12 + 32 + 52 + … + (2n – 1)2 =
For n = 1, we have
P(1) = 12 = 1 = , which is true.
Let P(k) be true for some positive integer k, i.e.,
P(k) = 12 + 32 + 52 + … + (2k – 1)2 = _____________ (1)
We shall now prove that P(k + 1) is true.
Consider
{12 + 32 + 52 + … + (2k – 1)2} + {2(k + 1) – 1}2
[Using (1)]
Thus, P(k + 1) is true whenever P(k) is true.
Hence, by the principle of mathematical induction, statement P(n) is true for all natural numbers i.e., n.
4. DIVISIBILITY PROBLEMS
To show that an expression is divisible by an integer
(i) If a, p, n, r are positive integers, then first of all we write
(ii) If we have to show that the given expression is divisible by c.
Then express, , if some power of has c as a factor.
, if some power of has c as a factor.
, if some power of has c as a factor.
Illustration -8
For every natural number n, 11n+2 + 122n+1 is divisible by
(A) 133 (B) 123 (C) 91 (D) none of these
Solution
(A).
Let P(n) = 11n+2 + 122n+1
P(1) = 113 + 123 = 3059 which is divisible by 133.
Let P(k) = 11k+2 + 122k+1 be divisible by 133.
P(k+1) = 11k+3 + 122k+3 = 11k+2.11 + 122k+1 144,
= 11.11k+2 + (133 + 11) 122k+1
= 11[11k+2 + 122k+1] + 133.122k+1
= 11.P(k) + 133.122k+1
P(K) is divisible by 133 also 133.122k+1 is divisible by 133. Hence, P (k + 1) is also divisible by 133. Hence, by mathematical induction, the result is true for all n.
Illustration -9
For every natural number n, 52n + 2 –24n – 25 is divisible by
(A) 502 (B) 223 (C) 471 (D) 576
Solution
(D)
Let P (n) = 52n + 2 –24n –25
Then P (1) = 54 –24 –25 = 576
Then P (1) is divisible by 576
Now assume that P (k) is divisible by 576, that is assume
P (k) = 52k + 2 – 24k – 25 = 576m ……(1)
where m is a positive integer.
P (k + 1) = 52(k + 1) + 2 – 24(k + 1) – 25 = 52.52k + 2 – 24k – 49
= 25[52k + 2 – 24k – 25] + 25.24k + 25.25 – 24k – 49 = 25P (k) + 576k + 576
= 25.576m + 576(k + 1) by (1) = 576(25m + k + 1)
Hence P (k + 1) is divisible by 576.
Hence by mathematical induction, the result is true for all n.
Illustration -10
is divisible by (where n ∈ N)
(A) 2x (B) (C) (D) All of these
Solution
(B)
From above it is clear that is divisible by .
Trick: . Put n=2 and x=3; Then
Is not divisible by 6, 54 but divisible by 9. Which is given by option (c) = .
Illustration -11
The greatest integer which divides the number is
(A) 100 (B) 1000 (C) 10000 (D) 100000
Solution
(C)
From above it is clear that, is divisible by
5. APPLICATIONs OF MATHEMATICAL INDUCTION
SOME IMPORTANT POINTS
1. A.P. Series : a + (a + d) + (a + 2d) +……….
i) nth term =
ii) Sum of first n terms of an A.P.
= (where a is first term, d is common difference of an A.P.)
2. G.P. Series : a + ar + ar2 + ar3 +……..
i) nth term =
ii) Sum of first n terms =
iii) Sum of infinite terms =
3. Arithmetico – Geometric series (A.G.P.) :
a+(a+d).r+(a+2d).r2+…….+(a+(n – 1)d).rn-1
i) nth term of the series =
ii) Sum of n terms =
iii) Sum of infinite terms =
4.
i)
ii) sum of n terms =
5. For a sequence,
the differnece of consecutive terms are in A.P or G.P then nth term of given series are in the form of where a, b, c to be determined.
6. In finding nth term of the series, in the suitable option
n = 1 gives the Ist term of the series
n = 2 gives the IInd term of series.
7. In finding the sum of n terms of the series in the suitable option
n=1 gives the Ist term of the series
n=2 gives the sum of first 2 terms of the series
n=3 gives the sum of first 3 terms of the series.
8. To test the divisibility of the given expression put n = 1 and n = 2 in the given expression and get their values and G.C.D or H.C.F. of these two values gives the required divisor.
9. If the series is given upto n terms then begin the verification with n = 1, if the series is given upto (n – 1) terms, then begin the verification with n = 2. If the series is given upto (n – 2) terms, then begin the verification with n=3 etc.
10. =
11. =
12.
13. The sum of cubes of three consecutive natural numbers is always divisible by 9
14. For all positive integral values of n , is divisible by x – y.
15. For all positive integral values of n, is divisible by x + y.
16. For all positive integral values of n, is divisible by x + y.
17. is divisible by
18. is divisible by where P is prime.
19. n is any odd integer then is divisible by 24.
20. The product of “n” consecutive natural numbers is always divisible by n!.
21. If x, y, m are positive integers then x is said to be congruent of y modulo m if x – y is divisible by m and is denoted by
22. Suppose it is given F(n) > G(n) or
We have to prove that
F(n +1 ) > G(n + 1) or
or
Illustration -12
For all n ∈ N, 2nCn
(A) < 4n (B) > 4n (C) > 2n + 1 (D) none of these
Solution
(A)
To show 2nCn < 4n
F(n) = 4n, G(n) = 2nCn
F(n+1) = 4n+1, G(n+1) = 2n+2Cn+1
= 4. . ( since 2n + 2 > 2n + 1 )
Illustration -13
For all-natural numbers n greater than 1, the value of
(A) (B) (C) (D)
Solution
(C). For n = 2,
Hence it holds for n = 2.
Assume the result to hold for n = k
For n = k+1,
Now, if we show that
then we are through.
Hence the result is true for n = k + 1.
Hence, by mathematical induction, the result is true for all n.
Illustration -14
For what natural number n, the inequality 2n > 2n + 1 is valid?
(A) n 3 (B) n > 1 (C) n = 2 (D) n > 5
Solution
(A)
For n = 1, 2 < 2 + 1
n = 2, 4 < 5
n = 3, 8 > 7
so the result is true for n = 3
assume the result is true for n = k > 3, i.e.
2k > 2k + 1
So, P (k + 1) = 2k + 1 = 2.2k > 2.(2k + 1) = 4k + 2
= [2(k + 1) + 1] + (2k –1) > 2(k + 1) + 1 as 2k –1 > 0, since k > 3
∴ The result is true for n = k + 1
∴ By the principal of mathematical induction, the result holds .
Illustration -15
If x + y = a + b, x2 + y2 = a2 + b2, then xn + yn = an + bn
(A) (B) n 4 (C) n 3 (D) none of these
Solution
(A)
Let P(n) xn + yn = an + bn
P(1) x + y = a + b … (1)
P(2) x2 + y2 = a2 + b2 … (2)
Hence P(1) and P(2) are true. Assume the result to be true for n k.
⇒ x k – 1 + yk – 1 = ak – 1 + bk – 1 and xk + yk = ak + bk
In order to prove that P(k + 1) is true, we write
xk + 1 + yk + 1 = x(ak + bk – yk) + y(ak + bk – xk)
= (ak + bk) (x + y) – xy (xk – 1 + yk – 1)
= (ak + bk) (a + b) – xy (ak – 1 + bk – 1)
Now from (1) and (2) xy = ab ⇒ xk + 1 + yk + 1 = ak + 1 + bk +1
which is the desired R.H.S. for P(k + 1).
Hence, by mathematical induction, the result is true for all n.
Illustration -16
If u1 = cos θ, u2 = cos 2θ and un = 2un –1 cosθ – un –2 for n > 2. Then un
(A) tan nθ (B) cot nθ (C) sin nθ (D) cos nθ
Solution
(D)
We have to prove that un = cos nθ n N
Clearly u1 = cos θ, u2 = cos 2θ
So the result is true for n = 1 and n = 2 …(1)
Now assume the result for 2 < n k …(2)
Then uk + 1 = 2ukcosθ – uk –1
= 2 cos kθ cosθ – cos (k –1)θ Using (2)
= cos (k + 1)θ + cos (k –1)θ –cos (k –1)θ = cos (k + 1)θ …(3)
Hence the result is true for n = k + 1
Hence by mathematical induction the result is true for all n ∈ N.
Illustration -17
Let , use mathematical induction, Im
(A) (B)
(C), m = 0, 1, 2… (D) m, m = 0, 1, 2 …
Solution
(D).
The result is true for m = 1, 2. Let the result be true for m k.
Now, 2Ik – Ik – 1 – Ik + 1
=
=
= =
=
⇒ The result is true for m = k + 1.
Hence, by mathematical induction, the result is true for all n.